CLUSTER APPROACH AS ONE OF DETERMINANTS FOR INCREASING COMPETITIVENESS OF RIGA FREEPORT - Kasalis, Edgars; Kassalis, Ivars; Kasalis, Jānis (Ekonomika, 2011)
The cluster-based approach offers a new way of dividing and understanding an economy and competitiveness. The main objective of the present study was to reveal the influence of industrial clusters on Freeport’s of Riga business competitiveness and integrated development. The cluster environment stimulates competitiveness and competition inside the cluster and the industry. One of the reasons for the current problems of Latvia’s competitiveness is the low level of business entities’ co-operation and business integration in the national economy of Latvia and the Freeport of Riga in particular. Companies are isolated in their approaches to increasing their competitiveness and entering the global market. In many cases it is too hard a task for a single company. Authors formulate the business entities’ co-operation and integration as a gateway to an integrated development and higher competitiveness in the global market. The cluster environment stimulates the integrated development of all business entities within the cluster. The article was written using scientific, normative and legal sources and data, systemizing good practice in other branches, as well as the results on authors’ systematic researches on the topic. The monographic method, method of logical analysis and synthesis, analysis of statistical information and the expert method wre applied.